A New Chlorinated Phenolic Compound From the Antarctic Lichen, Pertusaria dactylina ... - Koo, Man H.; Kim, Min J.; Seo, Jae E.; Kim, Ji H.; Han, Se J.; Kim, Il C.; Lee, Jun H.; Youn, Ui J. (SAGE Journals, 2020)
A new chlorinated phenolic compound, methyl-3-chloro-2-hydroxy-4-methoxy-6-pentylbenzoate ( 1 ) and 4 known compounds ( 2 - 5 ) were isolated from the Antarctic lichen, Pertusaria dactylina ( Pertusariaceae ). The structure of the new compound was determined by means of One-dimensional and two dimensional nuclear magnetic resonance (1D and 2D NMR) and high-resolution fast atom bombardment mass spectrometry (HRFABMS) experiments. The antimicrobial activities of compounds 1 to 5 against Staphylococcus aureus and Candida albicans were evaluated. The results showed that compound 1 exhibited a weak inhibitory effect against C. albicans with an IC 50 value of 67 ± 7 μg/mL. ...